Social Factors associated with Relapse in Psychotic Patients Attending Teaching Hospitals in AL-Furat Al-Awsat Governorates (Medico Legal Update, 2020)
Background: The relapse in mental disorders is extremely painful and costly for the patient and his familyas well as for the community. These frequent readmissions are strain on the health institutions and on theMinistry of Health Budget.Objectives: To find out the relationship between the social factors of relapse and sociodemographic data ofpsychotic patients attending teaching hospitals in AL_Furat Al-Awsat Governorates.Methodology: The design was (Descriptive-Correlational) used to describe the variables and therelationships that occur among them in this study. The sample was (a non-probability) purposive of (181)relapsed psychotic patients were selected from our patients centers from teaching hospitals in AL_FuratAl-Awsat Governorates, during the period from 9th May 2019 to 20th August 2019. The instrument includedtwo parts: sociodemographic variables and the social factors associated with relapse. The researcher useddescriptive statistics tools such as frequency, percentage, mean of score and used in inferential statistics suchas Chi-Square.Results: The findings of the study indicate that (45.86%) of the sample their diagnosis was schizophrenia,(25.97%) were schizoaffective and (11.60%) were major depressive disorder with psychotic features. Also,the findings of the study indicate that (58.6%) of the study samples they have poor social factors, while(24.3%) they have moderate social factors and (17.1%) they have good social factors.Conclusion: There is a high significant relationship between the most sociodemographic data and socialfactor (that included family support and financial factors).